Geotechnical engineering development in Asia - Mahadzer Mahmud; Universiti Teknologi Malaysia. Fakulti Kejuruteraan Awam; Regional Conference in Geotechnical Engineering (GEOTROPIKA) (4th : 1997 : Johor Bahru) (Sekudai : Universiti Teknologi Malaysia, 1997)
08